Identification of the Corticospinal Tracts Achieved Using Blood-oxygen-level–dependent and Diffusion Functional MR Imaging in Patients with Brain Tumors - Holodny, Andrei I. (AJNR Am J Neuroradiol, 2001)
Summary: Diffusion-weighted MR imaging was used to delineate the corticospinal tract (CST) successfully and to depict its relationship to adjacent brain tumors. The CST was defined by a method by which it seems possible to delimit the distance from the CST to the main tumor mass and to show displacement and infiltration of the tract by the neoplasia. This information cannot be gathered from routine anatomic MR imaging.